Assessing metabolic syndrome in people with ID (intellectual disabilities) on antipsychotic medication. (30th July 2014) - Carballedo, A.; Doran, A.; Doyle, M.; Flavin, S.; Tyrrel, J.; Kelly, F.; Guerin, S.; Dodd, P.
Abstract : Aims: To identify whether clinical information routinely collected and recorded on clinical files is available for the identification of metabolic syndrome and to assess the prevalence of risk factors for the syndrome in a sample of people with intellectual disabilities (ID) and mental illness treated with antipsychotic medication. Methods: A retrospective analysis was performed for 76 adults with ID and comorbid mental illness, for whom treatment with antipsychotic medication was established. Statistical analysis was performed using SPSS 16.0. The Student t -test for parametric data and χ 2 -test for non-parametrical data were used. Results: Five of the six criteria for metabolic syndrome were available in all or a high proportion of the files, however no measurement for waist circumference was recorded in any of the files. Aripiprazole appears to be the least risky antipsychotic for metabolic syndrome. Conclusion: It is important to develop a systematic protocol to record diagnostic variables for metabolic syndrome in at risk populations such as those with ID and mental illness treated with regular antipsychotics.